2012
DOI: 10.5923/j.statistics.20120205.02
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Categorical Panel Data

Abstract: AbstractsIn some categorical tables, one of the classifying variables may be at least ordinal (ran ked) arising fro m a follow-up o r any similar study. The other classifying variab le(s) may be that which separates the population into groups using variables such as gender, race or location, or a co mbination of some of them. The counts obtained this way are analyzed recognizing that one of the variables is nearly metric and must be used and interpretation becomes easier when appropriate model is fitted to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 8 publications
(3 reference statements)
1
3
0
Order By: Relevance
“…The findings of this study are in line with studies from various research included in the literature review. The findings of this study complement a study by Adejumo, Abioye & Tar (2016) on the adoption of computer assisted language learning software which asserts that computer assisted learning, similar to other instructive software has the possibility to aid, hasten, stimulate, and develop language skills.…”
Section: Effect Of Computer Assisted Learning On Learners' English Wr...supporting
confidence: 75%
See 1 more Smart Citation
“…The findings of this study are in line with studies from various research included in the literature review. The findings of this study complement a study by Adejumo, Abioye & Tar (2016) on the adoption of computer assisted language learning software which asserts that computer assisted learning, similar to other instructive software has the possibility to aid, hasten, stimulate, and develop language skills.…”
Section: Effect Of Computer Assisted Learning On Learners' English Wr...supporting
confidence: 75%
“…A study by Adejumo, Abioye, and Tar (2016) among hearing secondary students in Nigeria showed that for one to successfully acquire a second or foreign language, the choice of a learning strategy that is effective is important. Hence, computer assisted learning resources can be adopted to facilitate the learning process of developing writing skills.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Similarly, the World Health Organization; WHO (2019) stated that barriers to the application of nursing instruction among nursing students include; (91.4%) lack of sufficient information about the concept of nursing instruction, (74.6%) lack of belief in caring for patients according to the nursing instruction, (71.4%) lack adequate knowledge about the nursing instructions, and (69.8%) lack interest in applying the nursing instructions which shows the gap between theory and practice. A recent Nigerian study reported that insufficient academic mentorship and suboptimal clinical exposure have emerged as prominent concerns (Adejumo et al, 2023). To the best of our knowledge, existing evidence in this domain predominantly originates from developed countries; however, there is a notable gap in the literature regarding studies investigating nursing students' perceptions and adherence to clinical practice, specifically within Nigeria.…”
Section: Introductionmentioning
confidence: 99%
“…In order to reduce cost of production of animal products, cheap and non-conventional feed ingredients have been assessed and the search is on-going (Babayemi and Bankole 2009;Adejumo and Bamidele, 2012;Adebiyi et al, 2018). Soybean is widely used as a protein source for monogastric animals, particularly, poultry and swine.…”
Section: Introductionmentioning
confidence: 99%